แรงจูงใจในการเลือกเล่นกีฬายิมนาสติกของนักกีฬายิมนาสติกในการแข่งขันกีฬาแห่งชาติ ครั้งที่ 39 - แก้วปัญญา, ราชวัตร; สุทธิพันธุ์, วัฒนา; เลวัลย์, นำชัย (Community and Social Development Journal, 2011)
บทคัดย่อภาษาไทยไม่สมบูรณ์ Motivation for Selecting to Play Gymanstics of Gymanstics Athletes in the 39th National Games The purpose of this research was to study and compare the Motivation for Selecting to play Gymnastics of Gymnastics athletes in the 39th national games. The subjects of 167, Men Artistic Gymnastics 100 persons, Rhythmic Gymnastics 33 persons and Aerobic Gymnastics 34 persons. The thing was used for Integration results is questionable form which researcher have created and analyzed results by Distributing Frequency, Percentage, Standard deviation, and T-test. The results 1. Motivation for selecting to play Gymnastics of Gymnastics Athletes in the 39th National games is intrinsic motivation and extrinsic motivation are very good quality for both. 2. Motivation for selecting to play Gymnastics of Gymnastics Athletes in the 39th National games more than men and women players were not different. 3. Motivation for selecting to play Gymnastics of Gymnastics Athletes n the 39th National games who have an experience less than 4 years with Athletes in who have an experience more than 4 years results aren’t different.